Administrative Reform and Its Relationship with Occupational Stress In Physical Education and Sport Sciences’ Faculty Members - Abed al ameer, Layla; Musa, sindus; Abood, Manal (Journal of Physical Education, 2019)
The research aimed at identifying the reality of administrative reform from assisting deans and head of departments’ point of view as well as identifying the relations between administrative reform and occupational stress reform from assisting deans and head of departments’ point of view. The researchers used the descriptive method on (84) administrative leaders including assisting deans and head of departments in colleges and departments of physical education and sport sciences’ colleges.